Renal pleomorphic undifferentiated sarcoma: A rarity - Suresh Kumar; Punit Bansal; Punit Tiwari; Anup K Kundu (Saudi Journal of Kidney Diseases and Transplantation, 2012)
A 70-year-old male presented with progressive weight loss for eight months. Radiological imaging showed a large tumor in the right kidney. The patient underwent right open radical nephrectomy and histopathology revealed pleomorphic undifferentiated sarcoma (PUS) earlier known as malignant fibrous histiocytoma (MFH). One year after surgery, the patient developed pulmonary metastasis. Unfortunately, the patient died after six months.